2016
DOI: 10.18632/oncotarget.12948
|View full text |Cite
|
Sign up to set email alerts
|

FEN1gene variants confer reduced risk of breast cancer in chinese women: A case-control study

Abstract: This study aimed to assess the associations of two common Flap endonuclease 1 (FEN1) polymorphisms (rs4246215 and rs174538) with breast cancer risk in northwest Chinese women. We conducted a case-control study with 560 breast cancer patients and 583 age-matched healthy controls from Northwest China. Odds ratios (ORs) and 95% confidence intervals (95% CIs) were used to estimate the associations. We found a significantly reduced risk of breast cancer associated with T allele of rs4246215 (allele model: OR 0.81, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…We then assessed the DNA concentrations by spectrophotometry (DU530 UV/VIS spectrophotometer, Beckman Instruments, Fullerton, CA). The Multiplexed SNP Mass EXTEND assay was designed by Sequenom Mass‐ARRAY Assay Design (version3.0, Agena Bioscience, San Diego, CA), according to previous studies . Sequenom Mass‐ARRAY RS1000 and Sequenom Typer 4.0 software were used to genotype the SNPs and for the data analyses .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We then assessed the DNA concentrations by spectrophotometry (DU530 UV/VIS spectrophotometer, Beckman Instruments, Fullerton, CA). The Multiplexed SNP Mass EXTEND assay was designed by Sequenom Mass‐ARRAY Assay Design (version3.0, Agena Bioscience, San Diego, CA), according to previous studies . Sequenom Mass‐ARRAY RS1000 and Sequenom Typer 4.0 software were used to genotype the SNPs and for the data analyses .…”
Section: Methodsmentioning
confidence: 99%
“…The Multiplexed SNP Mass EXTEND assay was designed by Sequenom Mass-ARRAY Assay Design (version3.0, Agena Bioscience, San Diego, CA), according to previous studies. [27][28][29][30] Sequenom Mass-ARRAY RS1000 and Sequenom Typer 4.0 software were used to genotype the SNPs and for the data analyses. 31 The primers of each SNP are presented in Table S1.…”
Section: Genotyping Assaymentioning
confidence: 99%
“…The clinical and demographic characteristic of BC patients and controls were described in our previous studies. 25 , 26 The cases and controls were matched by age (Student’s t -test, P =0.612). As shown in Table 1 , there was no significant difference in the distribution of menopausal state between the two groups (χ 2 test, P =0.716).…”
Section: Resultsmentioning
confidence: 99%
“…Association study with 1840 lung cancer patients and 1958 controls further revealed that these two FEN1 SNPs conferred genetic susceptibility to lung cancer [ 49 ]. Moreover, some evidence was further observed to consolidate the contribution of the rs174538 and rs4246215 to the risk of different types of cancer [ 25 , 36 , 37 , 39 ]. Especially, these two SNPs were shown to decrease breast cancer risk in Chinese [ 25 ]and Iran [ 37 ] populations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some evidence was further observed to consolidate the contribution of the rs174538 and rs4246215 to the risk of different types of cancer [ 25 , 36 , 37 , 39 ]. Especially, these two SNPs were shown to decrease breast cancer risk in Chinese [ 25 ]and Iran [ 37 ] populations. The prevalence of the studied SNPs varies among different ethnic groups (data not shown).…”
Section: Discussionmentioning
confidence: 99%